National special education policy: Scope review protocol (Research, Society and Development, 2023)
This article presents the protocol for a Scoping Review on the National Special Education Policy through Decree No. 10,502, dated September 30, 2020, which establishes the creation of the National Policy on Special Education: Equitable, Inclusive, and Lifelong Learning, with legal tensions. The aim is to examine the development, scope, and clear understanding of publications in research, seeking answers in the literature about the content of publications in the field of National Special Education Policy from 2020 onwards. This is a qualitative study of a Scoping Review, following the methodology of the Manual for Evidence Synthesis by the Joanna Briggs Institute (JBI). The PCC (Population, Concept, Context) strategy will be used to define the research question and inclusion and exclusion criteria. The search and database selection strategy will be developed with the guidance of a specialist in digital search strategy and will include multiple databases such as Cumulative Index to Nursing and Allied Health Literature (CINAHL), National Library of Medicine (PubMed), SCOPUS, WEB OF SCIENCE, MEDLINE, EMBASE, Scientific Electronic Library Online (SCIELO), and Google Scholar. Descriptors and synonyms will be used according to the Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH). This protocol has been registered on the Open Science Framework (OSF) under the DOI: 10.17605/OSF.IO/HJD3C. It is expected that this protocol will contribute to the findings regarding the national policy of Special Education in Brazil.